2022
DOI: 10.1021/acsomega.2c03127
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Pseudomonas aeruginosa ATP Synthase Inhibitors

Abstract: New antibiotics with unique biological targets are desperately needed to combat the growing number of resistant bacterial pathogens. ATP synthase, a critical protein found in all life, has recently become a target of interest for antibiotic development due to the success of the anti-tuberculosis drug bedaquiline, and while many groups have worked on developing drugs to target bacterial ATP synthase, few have been successful at inhibiting Pseudomonas aeruginosa (PA) ATP synthase specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…In previous work, we conducted an initial SAR study of quinolines derivatized at the C1 and C2 positions and their inhibition of PA ATP synthesis activity, and we found that bulky constituents at C1 and C2 and hydrogen bonding capability at C2 related to stronger inhibition. Based on those results, we generated additional quinoline derivatives that maintained (methyl sulfide) or increased (benzyl sulfide) hydrophobic bulk at C1 and introduced bulky constituents at C2.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In previous work, we conducted an initial SAR study of quinolines derivatized at the C1 and C2 positions and their inhibition of PA ATP synthesis activity, and we found that bulky constituents at C1 and C2 and hydrogen bonding capability at C2 related to stronger inhibition. Based on those results, we generated additional quinoline derivatives that maintained (methyl sulfide) or increased (benzyl sulfide) hydrophobic bulk at C1 and introduced bulky constituents at C2.…”
Section: Discussionmentioning
confidence: 98%
“…Previously, we synthesized a series of C1 and C2 quinoline analogs in order to determine if ATP synthesis inhibition could be a useful antibiotic development target in PA . From this study, we found that 6 of the quinolines were able to inhibit ATP synthesis in PA vesicles, with compound 1 (Figure C), which has a methyl sulfide at C1 and a l -tyrosine methyl ester at C2, being among the most active of the compounds surveyed.…”
mentioning
confidence: 99%
“…In addition, ATP synthase subunits have been reported as an antibacterial target in Pseudomonas aeruginosa and others. 48 , 49 In addition, a severe reduction in ATP synthesis in Enterococcus faecalis and E. faecium was observed when treated with terpenoids from Salvia tingitana . 50 Our findings suggest that JR or MA contain phyto-molecules that could target the production of ATP and thus impart effects on energy-dependent metabolic pathways in P. gingivalis .…”
Section: Discussionmentioning
confidence: 99%
“…The downregulation of ATP synthase subunits would suppress the normal energy-dependent metabolic processes and growth of P. gingivalis . In addition, ATP synthase subunits have been reported as an antibacterial target in Pseudomonas aeruginosa and others. , In addition, a severe reduction in ATP synthesis in Enterococcus faecalis and E. faecium was observed when treated with terpenoids from Salvia tingitana .…”
Section: Discussionmentioning
confidence: 99%
“…Due to this complexity, synthetic success and compound characterization were limited and having discrete phases prevented students from being able to troubleshoot their designs when synthetic challenges occurred. Therefore, few compounds (<10) advanced as far as biological evaluation and only 2 compounds were able to be published . Additionally, since students proposed their own mini-structure–activity relationship (SAR) studies, even the compounds that were generated were not cohesive enough to draw conclusions.…”
Section: Unc Asheville Drug Discovery Project Laboratorymentioning
confidence: 99%